Pengenalan Kartu Identitas Anak (KIA) pada Warga Kelurahan Pasuluhan - Desty Endrawati Subroto; Sri Rohayati; Ina Agustina (jurnal ABDIMAS Indonesia, 2024)
This research aims to explain the importance of knowing Children's Rights and Issuing Child Identity Cards (KIA) to residents of Pasuluhan Village. A Child Identity Card (KIA) is a document that describes a child's official identity as proof of a child aged 0-17 years and unmarried, issued by the District/City Population and Civil Registration Service in Banten Province. Meanwhile, the type of research used is a descriptive method with qualitative analysis, namely a type of research through problem-solving procedures which are investigated by describing, depicting the current situation surrounding the research object based on facts. Based on the results of this research, it is known that Pasuluhan sub-district residents who have children do not yet know and issue Child Identity Cards (KIA) at the Serang City Population and Civil Registry Service. So, it can be seen that the population of Pasuluhan sub-district who know and have KIA is still low. This is because there are still many people who consider Child Identity Cards to be unimportant, and think that it is sufficient to use a birth certificate as identity, when issuing child identity cards in accordance with Minister of Home Affairs Regulations. State Number 2 of 2016 as well as conducting outreach on the importance of KIA to the community, especially to posyandu cadres and schools in rural areas so that people understand the importance of children's identity cards, then human resources are emphasized more in implementing this policy to provide services to the people of Serang City and increasing supervision of Child Identity Card issuance services. Better socialization is considered important to increase public understanding of the benefits and procedures for making KIA. Based on these findings, it is recommended that the KIA program continue to be improved and perfected so that it is more efficient and provides greater benefits for the community.